PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI EKOSISTEM DI KELAS V SDN 8 CAKRANEGARA - Safoan, Ahmad; Nurul Kemala Dewi; Nurwahidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Project Based Learning learning model on student learning outcomes on ecosystem material in class V of SDN 8 Cakranegara. This study is a quasi-experimental study with a nonequivalent pre-test and post-test control group design. Data collection techniques use multiple-choice test techniques and observation sheets for the implementation of the Project Based Learning learning model. The research sample used in this study were all fifth-grade students of SDN 8 Cakranegara with a total of 41 students. The data analysis technique uses SPSS version 25 with the results of the hypothesis using an independent sample t-test with a significance of 0.05, the sig. (2-tailed) is 0.002 smaller than 0.05. So that the decision making used is Ho is rejected and Ha is accepted, which means there is an influence of the Project Based Learning learning model on student learning outcomes on ecosystem material in class V of SDN 8 Cakranegara.